2008
DOI: 10.1111/j.1939-1676.2008.0193.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Electrohydraulic Lithotripsy in 28 Dogs with Bladder and Urethral Calculi

Abstract: Background: Electrohydraulic lithotripsy (EHL) has been used as an alternative to cystotomy in human medicine to remove urinary calculi. This prospective study evaluated the efficacy and safety of EHL to remove urinary calculi in dogs.Hypothesis: EHL is an efficient and safe method of treatment of bladder and urethral calculi in dogs. Methods: Dogs presented between January 1, 2005 and June 1, 2007 with lower urinary tract calculi diagnosed by radiographs or ultrasound examination were included in the study. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Ureteroscopic fragmentation of ureteral stones by use of intracorporeal lithotripsy is a popular, effective, minimally invasive technique and is considered to be the treatment of choice for lower ureteral stones [5]. Previous studies have reported success rates ranging from 72 to 100% [4,5,14,15], which is similar to the success rate in our study for patients who were treated by URS with EHL (98.5%).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Ureteroscopic fragmentation of ureteral stones by use of intracorporeal lithotripsy is a popular, effective, minimally invasive technique and is considered to be the treatment of choice for lower ureteral stones [5]. Previous studies have reported success rates ranging from 72 to 100% [4,5,14,15], which is similar to the success rate in our study for patients who were treated by URS with EHL (98.5%).…”
Section: Discussionsupporting
confidence: 87%
“…The more lamellated and harder a stone, the more difficult it is to break [1,4]. Stone surface characteristics may also play a role in fragmentation efficiency because rough stones have been reported to fragment more easily than smooth ones [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With proper case selection, all uroliths can be fragmented by laser lithotripsy and removed in approximately 85% of male dogs and nearly all female dogs. [24][25][26][27] In the author's experience this technique is best suited to female dogs with a small number of bladder or urethral uroliths and male dogs with ureteroliths. Animals with larger stone burdens are better suited for a PCCL procedure (see later discussion).…”
Section: Laser Lithotripsymentioning
confidence: 95%
“…Publications of the use of these modalities in small animal patients are scarce, and more are under way. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] This section will discuss some additional equipment that is used for these interventional modalities that has not been previously discussed, and each area of the urinary tract will be addressed. The sections will separately expand on the current veterinary literature and procedural descriptions ( …”
Section: Interventional Radiology and Interventional Endoscopy Of Thementioning
confidence: 99%